2016
DOI: 10.1017/s2040174416000076
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal maternal mental health and fetal growth restriction: a systematic review

Abstract: Maternal mental disorders during pregnancy are associated with a range of adverse health outcomes for offspring. This systematic review examines studies reporting on the relationship between maternal depression, anxiety or stress during pregnancy and fetal growth measured during pregnancy using ultrasound biometry. A systematic search of PsycINFO, Medline, Scopus, Web of Science and Embase was conducted and 1575 records were identified, with nine studies meeting inclusion criteria gathering data from over 7000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 78 publications
3
55
0
2
Order By: Relevance
“…The presence of these symptoms at high levels can lead to unfavorable maternal and perinatal outcomes. (2)(3)(4)(5) The least frequent was the thought about injuring oneself. However, its presence at all stages shows the importance of a specific screening tool to identify pregnant women at risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of these symptoms at high levels can lead to unfavorable maternal and perinatal outcomes. (2)(3)(4)(5) The least frequent was the thought about injuring oneself. However, its presence at all stages shows the importance of a specific screening tool to identify pregnant women at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Depression may persist in the postpartum period and compromise parental behavior, the relationship with the partner and family, the process of mother-child bonding, and the child's cognitive, motor and psychosocial development. (2)(3)(4)(5) Studies on depression and its effects in the prenatal period are recent, dating back two decades, with an increase thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…Physical/sexual abuse may cause a range of health problems such as sexually transmitted infections, chronic pains, fractures as well as stress, anxiety and depression,9 and inability to be a good parent after childbirth 6. Furthermore, violence during pregnancy has been associated with fetal growth restriction, adverse pregnancy outcomes and childhood growth impairment 10 11. Depression and stress may subsequently lead to increased levels of stress hormones during pregnancy and reduced placental circulation 10.…”
Section: Introductionmentioning
confidence: 99%
“…It is defined as having a weight at two standard deviations (tenth percentile) below that of a normal fetus, or at <2.5 kg after 37 weeks of pregnancy (Seravalli and Baschat, 2015). The cause for abnormal fetal size may be either extrinsic (placenta, matrix) or intrinsic to the fetus itself (Lewis et al, 2016;Xiao et al, 2016). Studies have shown that FGR is the second leading cause of deaths among fetuses during the perinatal period, with a threefold increase in mortality rates as compared to that of a normal neonate (Boulet et al, 2006).…”
Section: Introductionmentioning
confidence: 99%